Long-term outcome of radiation therapy for locoregional recurrence of upper tract urothelial carcinoma after nephroureterectomy - Ho-Hsiang Chang; Hao-Lun Luo; Yu-Li Su; Fu-Min Fang; Chong-Jong Wang; Chun-Chieh Huang (BMC Urology)
Abstract Background The objective was to evaluate the survival outcomes associated with radiation therapy (RT) in cases of postoperative locoregional recurrence of upper tract urothelial carcinoma (UTUC) following radical nephroureterectomy (RNU). Methods A total of 30 patients undergoing RT for local or regional recurrence of UTUC after RNU from 2002 to 2017 were enrolled. The median follow-up time for patients who survived was 5.9 years. The application of RT comprised two intents: (1) salvage RT for patients who did not respond to chemotherapy or who did not receive chemotherapy, and (2) consolidation RT for patients who showed complete or partial response to chemotherapy. Overall survival (OS) since recurrence, locoregional progression-free survival (LRPFS) after RT, and distant metastasis-free survival (DMFS) after RT were evaluated. Univariate Cox regression analysis was applied. Results The median OS since recurrence was 40.0 months, and the 5-year OS, LRPFS, and DMFS rates were 46.6%, 45.0%, and 36.7%, respectively. For 14 patients who underwent salvage RT, the 5-year OS, LRPFS, and DMFS rates were 28.6%, 21.4%, and 21.4%, respectively; for 16 patients undergoing consolidation RT, those rates were 63.5%, 65.8%, and 50.0%, respectively. In univariate analysis, consolidation RT and primary site in the ureter were significant prognostic factors for better OS and LRPFS; an age ≤ 60.0 years was also a significant factor for OS. There was no significant factor for DMFS. Conclusions The patients undergoing RT for postoperative locoregional recurrence of UTUC had promising survival outcomes. Future prospective randomized trials to verify the findings are needed.